In Immunological Reactions, Lipid Peroxidation and Antioxidant Activity (Literary Review) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
According to Selye, stress is a stress reaction that occurs as a non-specific response of the body to the action of extreme unfavorable factors - stressors. By its biological nature, stress has an adaptive orientation and activates protective mechanisms to prevent the pathogenic effect of adverse environmental factors on the body.